1998
DOI: 10.1136/oem.55.11.771
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic and adverse respiratory effects in children. SIDRIA Collaborative Group.

Abstract: Objectives-To investigate the relation between traYc indicators in the area of residence and the occurrence of chronic respiratory disorders in children. Methods-A population based survey was conducted in 10 areas of northern and central Italy (autumn 1994 to winter 1995) in two age groups (6-7 and 13-14 years). Information on several respiratory disorders and on traYc near residences was collected with a questionnaire given to children and to their parents. The sample analysed included 39 275 subjects (respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
169
0
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 35 publications
(26 reference statements)
17
169
0
9
Order By: Relevance
“…The first study [11] presented data for chronic cough and found a similar association of this rather unspecific symptom with truck traffic and black smoke exposure as with wheeze. The second study [15] found an association of truck traffic exposure with current wheeze, cough and persistent phlegm, but not with current asthma and not with wheezing episodes in the first two years of life. These authors concluded that air pollution from truck traffic increases the risk for a wide range of adverse respiratory effects but may have a more important role in respiratory infections than in the aetiology of asthma.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The first study [11] presented data for chronic cough and found a similar association of this rather unspecific symptom with truck traffic and black smoke exposure as with wheeze. The second study [15] found an association of truck traffic exposure with current wheeze, cough and persistent phlegm, but not with current asthma and not with wheezing episodes in the first two years of life. These authors concluded that air pollution from truck traffic increases the risk for a wide range of adverse respiratory effects but may have a more important role in respiratory infections than in the aetiology of asthma.…”
Section: Discussionmentioning
confidence: 85%
“…In this nonatopic subgroup, asthma may mainly be triggered or induced by viral infections. Some evidence suggests that the development of childhood respiratory tract infections is in fact related to increasing exposure to SO 2 , NO 2 and particles [3,4,15]. Alternatively, irritative symptoms due to higher pollution exposure may result in more frequent visits to a physician who may then be more likely to misclassify a bronchitic child as asthmatic.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Japan found that rate of asthma increased among girls living within 50 m of a trunk road (Shima et al, 2003), and an increased incidence of asthma during the follow-up period, that was significantly associated with atmospheric concentrations of nitrogen dioxide (a vehicular exhaust emission) (Shima et al, 2002). A study in Italy found that children who live on streets with a high frequency of truck traffic may experience adverse respiratory effects with increased lower respiratory tract infections early in life and wheezing and bronchitic symptoms at school age (Ciccone et al, 1998). In the Netherlands, cough, wheeze, runny nose, and doctor-diagnosed asthma were significantly increased for children living within 100 m of the freeway (van Vliet et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association between traffic volume and the number of hospital admissions for asthma (English et al, 1999), vehicle or truck traffic and self-reported symptoms of asthma (Weiland et al, 1994;Duhme et al, 1996), but others have found no association between asthma and traffic volume (Wilkinson et al, 1999). Truck and road traffic were related to chronic respiratory symptoms and reduced lung function in studies of adolescents (Wjst et al, 1993;Oosterlee et al, 1996;Van Vliet et al, 1997;Brunekreef et al, 1997;Ciccone et al, 1998). Most of these studies used traffic counts as a surrogate for exposure to vehicle emissions.…”
Section: Introductionmentioning
confidence: 99%